2019
DOI: 10.35408/comuybd.518307
|View full text |Cite
|
Sign up to set email alerts
|

Örgütsel Ustaliğin Müşteri̇ Odakli Hi̇zmet Davranişlari Üzeri̇ndeki̇ Etki̇si̇nde Hata Yöneti̇m Kültürünün Aracilik Rolü

Abstract: Within the literature, it is suggested that employee's tendency to exhibit customeroriented service behaviors based on the various individual and organizational

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
2
0
2
Order By: Relevance
“…Organizational ambidexterity skills of businesses that want to successfully maintain their existence in turbulent environmental conditions are explained with the metaphor of "people's ability to use both hands at the same time". Organizational ambidexterity is the capability of businesses to use their knowledge, skills and resources to the last point, and to become a master at discovering new development areas and ideas (Kanten & Kanten, 2019). The basic premise of organizational ambidexterity is that it considers multifaceted skill use as a vital paradigm that guarantees the future.…”
Section: Organizational Ambidexteritymentioning
confidence: 99%
“…Organizational ambidexterity skills of businesses that want to successfully maintain their existence in turbulent environmental conditions are explained with the metaphor of "people's ability to use both hands at the same time". Organizational ambidexterity is the capability of businesses to use their knowledge, skills and resources to the last point, and to become a master at discovering new development areas and ideas (Kanten & Kanten, 2019). The basic premise of organizational ambidexterity is that it considers multifaceted skill use as a vital paradigm that guarantees the future.…”
Section: Organizational Ambidexteritymentioning
confidence: 99%
“…Ulusal ve uluslararası alanda literatür taraması yapıldığında araştırmada ele alınan değişkenlerin bir arada kullanıldığı bir çalışmaya rastlanmamıştır. Ancak erteleme davranışı ile ilgili yapılan benzer çalışmaların sonuçlarına göre, sosyal medya bağımlılığı ile akademik erteleme davranışı arasında pozitif bir korelasyon olduğu (Akbaş Coşar ve Gedik, 2021), sosyal medya bağımlılığının erteleme davranışını artırdığı (Tekin, 2019), iş yaşam dengesi ile erteleme davranışı arasında negatif yönlü bir ilişkinin varlığı (Kanten, 2018) ortaya konmuştur. Bu sonuçlar çalışmadaki değişkenlerle birebir aynı olmasa da benzer değişkenler olduğu için araştırma sonuçlarını destekler niteliktedir.…”
Section: Sonuçunclassified
“…Ulusal alanyazında hata yönetimi kültürüne ilişkin çalışmalar (Güçlü Nergiz, 2015; Kanten ve Kanten, 2019;Serger, 2017;Sıcakkan Özerden, 2019;Yiğital, 2018) incelendiğinde bu çalışmaların işletme örgütlerinde yürütüldüğü ve bu çalışmalarda genel olarak Rybowiak vd. (1999), van Dyck (2000 ve van Dyck vd.…”
Section: öRgütlerde Hata Yönetimiunclassified
“…Schools need to have a culture of positive error management, where mistakes are not considered as a threat, but as an opportunity for new learning and innovation. Current studies (Frese & Keith, 2015;Guchait et al, 2012;Kanten & Kanten, 2019;Sıcakkan Özerden, 2019;van Dyck et al, 2005;Yiğital, 2018) have shown that error management culture is mostly studied in terms of business organizations. However, Nanto (2021) studied error management culture in the context of education and developed an Error Management Culture Scale.…”
Section: Extended Abstract Introductionmentioning
confidence: 99%